Effect OF Film Thickness And Annealing Time on Structural And Optical Propertieis Of The Oxides (Fe2030, Co304) And Their Mixtures - Maki, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Thin film technology is one of the most important technologiesthat have contributed to the development of semiconductors and theirapplications in several industrial fields. The Iron Oxides (Fe20) and(Co3O4) thin films and their applications are of importance, in that thesetwo materials are considered as important industrial materials, and usedin spectrally selective coating, temperature sensors, resistive heaters, andphoto cells.Thin films of Iron Oxide (Fe20,), Cobalt Oxide (Co304) andtheir mixtures in different ratios (75:25, 50:50, 25:75) were prepared bythe method of chemical spray pyrolysis deposition at different thicknesses(77s t S200) nm on cover-glass substrates: thickness of (1) mm attemperature (653)OK, and at temperature (753)oK for (one, and two) hour.The nature of the thin-filmssurfaces are examined by opticalmicroscopy, while the crystallinity of the compounds is examined by Xray diffraction (XRD)The results of KRD) have shown that the films of (Fe20,) and(Co304) and their mixtures are of amorphous structure. Annealingoperations led to transition of the films' structure from the amorphous to polycrystalline state. These obtained results were found inagreement with the American Standard for Testing Materials (ASTM).Film thickness, and annealing time were investigated, the results show thecrystallite size increases with the increase of the thickness of the thinfilmThe increase in the annealing time for more than one hour resultedin the appearance of some peaks in diffraction spectrum of the preparedfilms. This verifies that it is polycrystalline, and this increases the time toorganize itself in the crystalline lattice and decreases the crystallinedefect. This research also included the study of the optical properties ofthe prepared samples by recording the absorption and transmissionspectrum over the spectral range (200-900 nm, the optical energy gap forthe allowed direct transition was evaluated. In general, the optical energygap decreases with increase of the film thickness percentage of (Co3O4)in the sample, and it increases after annealingThe optical parameters are investigated and calculated such aoptical absorption coefficient, photon energy, and the width of localizedstates too. It is found that the values of absorption coefficient theincreases with increasing percentage of (Co3O4)